Respuesta :

Multiply each side of the given equation by ax−2 (so you can get rid of the fraction). When you multiply each side by ax−2, you should have:

24 x ^2 + 25x − 47 (−8x−3)(ax−2)−53

You should then multiply (−8x−3) and (ax−2) using FOIL.

24 x ^2 + 25x − 47= 8ax^2 − 3ax + 16x + 6 − 53

Then, reduce on the right side of the equation

24 x ^2 + 25x − 47= (8x − 3(ax - 2) - 53

Since the coefficients of the x^2-term have to be equal on both sides of the equation, −8a=24, or a=−3.

Your answer would be B
ACCESS MORE